Empirical Testing of the Implementation of Supply Chain Management and Successful Supporting Factors of Management Accounting Information Systems - Leny Suzan; Sri Mulyani; Citra Sukmadilaga; Ida Farida (International Journal of Supply Chain Management, 2019)
Abstract-This study aims to measure empirically tested conceptual models regarding the magnitude of intellectual capital influence, operational risk management, and business strategy on the effectiveness of management accounting information systems and their implications on the performance of a balanced scorecard based company. This research used sensus as sampling technique, it used all existing population. This research was conducted using a survey method in Banking Sectors in Indonesia based on the supply chain management. Data analysis was performed using Structural Equation Model (SEM) approach alongside a Linear Structural Relationship (Lisrel) analysis tool. The results of the study found that intellectual capital, operational risk management, and business strategy have a significant positive effect on the effectiveness of accounting information system, while its significance on the performance of balanced scorecard based company operational risk management and business strategy alone has a significant positive effect. While the effectiveness of accounting information systems are known to have significant implications on the company’s performance-based balanced scorecard.